URGENSI LITERASI TEKNOLOGI INFORMASI BAGI WIDYAISWARA PENDIDIKAN AGAMA ISLAM BDK ACEH MENGHADAPI ABAD 21 - ., Nurdin (Inovasi: Jurnal Diklat Keagamaan, 2019)
Today, mastery of technology or IT among educators especially in this case is the Islamic Education widyaiswara still looks low, this can be seen when the learning process in the classroom takes place, they are still confused about this especially when there are problems about IT, and this is a problem which must have a solution. This study aims to find out how urgent technology literacy is for widyaiswara Islamic Education in the Aceh Education and Training Center in the 21st Century and to know the efforts to improve technology literacy. The sample in this study was all widyaisawara PAI Balai Diklat Aceh totaling 7 people. This research includes library research and field research with the nature of descriptive-analytical research. Data collection techniques, namely observation and interviews, then after the required data collected is analyzed by deductive-inductive method. The research findings show that the culture of technology literacy among Islamic religious education lecturers is relatively low. Some efforts in increasing technology literacy for widyaiswara PAI in the 21st century are through love to read, write and research, love in the field of technology, instill the importance of technological literacy, encourage them to have books in the field of technology, instill that literacy to all sciences is God's command as stated in the Qur'an, Al-'Alaq verse 1-5.